Pengaruh Model Kooperatif Tipe Scramble Terhadap Hasil Belajar Siswa pada Pembelajaran Tematik Terpadu Di Kelas IV UPT SD Negeri 06 Pasar Taratak Pesisir Selatan - Hendriani, Maifit; Sasmuryanti, Rara (LP2M Universitas Adzkia, 2023)
This research is motivated by the low student learning outcomes in integrated thematic learning this is due to the absence of cooperation between students in the learning process, students are not accustomed to expressing their opinions and the lack of student involvement in the learning process so that the learning process is only teacher-centered (teacher centered) and learning only uses the lecture and question and answer method. The purpose of this study was to determine the effect of the Scramble-type cooperative model on student learning outcomes in integrated thematic learning in class IV UPT SDN 06 Pasar Taratak Pesisir Selatan. This type of research is a quantitative study with a Quasi Experimental design, using a posttest only control group design experimental design. Data collection in this study was an objective question in the form of multiple choice as many as 15 items, the data obtained were analyzed using t-test. Based on the results of this research, it can be seen that the t-count = 3.453 and t-table = 1.668 and the significant level is 5%. Based on the t-count > t-table (3.453 > 1.668) then H1 is accepted and HO is rejected. From the research results, it is proven that this scramble type cooperative model has an influence on student learning outcomes in integrated thematic learning in class IV UPT SDN 06 Pasar Taratak Pesisir Selatan for the academic year 2021/2022.